FACTORS CAUSING LOW STUDENT MOTIVATION: A SYSTEMATIC LITERATURE REVIEW - Aida Nur Fitria Khamima; Dodi Suryana; Abdul Kholiq (Universitas Pendidikan Indonesia, 2023)
Learning motivation is one of the factors that determine student success. Each student has different motivations when participating in learning at school. The differences in student learning motivation create teaching problems for teachers. Because each student brings different motivation when participating in learning. The purpose of this study is to record the factors that cause low student learning motivation and find the dominant factor in influencing student learning motivation. This research uses the Systematic Literature Review research method. The results showed that there are internal and external factors that affect students' low learning motivation.